Assessing protective factors to prevent post-discharge violent behaviour: Towards an assets-based approach for clinical risk management. (November 2021) - Doyle, Michael; Coid, Jeremy; Ullrich, Simone; Shaw, Jenny
Abstract: Medium secure forensic psychiatric units (MSUs) in the UK aim to be recovery-oriented to enable discharge to community-based services. Risk assessments are key to discharge planning, but clinical practice tends to focus on risk factors for violence rather than protective factors associated with a decrease in risk. The aims of this study were to investigate the reliability and validity of the Structured Assessment of Protective Factors (SAPROF) as a useful measure to support an assets-based approach when planning discharge from MSUs. A prospective cohort follow-up design was chosen for this study using a confidential inquiry design to ensure a total sample of all discharges. All forensic patients discharged from 32 NHS MSUs over a 12-month period were assessed at discharge and followed-up at six and 12 months post discharge. The occurrence and frequency of post-discharge violence were compared with discharge SAPROF scores. The inter-rater reliability between SAPROF raters was very high and the SAPROF significantly predicted community violence and scores were strongly correlated with violence frequency. The higher the SAPROF score the higher the protection against violence and the risk significantly diminished. Assessing protective factors is essential to identify assets and prevent violence with a focus on what makes somebody safe. This study supports the use of the SAPROF to inform discharge planning. Cultivating protective factors is likely to be motivating for patients and the SAPROF can provide an objective, reliable measure of internal, motivational and external assets that reduce risk and support defensible decision making at discharge.